Sociocultural Issues Experienced by Adults Learning Maltese as a Second Language - Jacqueline Żammit (IAFOR Journal of Education, 2022)
The pedagogy of language has since time immemorial majored in the use of pens and other printed materials. However, there occurred a separation of the teaching culture into two major categories; the “big C” and “little c”, meaning high and popular culture. Over the years, advancements in various pedagogical techniques have made this boundary separating the two cultures thinner and thinner. It is now blurred with the result that one may not tell which teaching culture is applicable in various circumstances. The leading cause of these changes is sociocultural issues. Present-day evaluations of the humanities have caused a shift towards a broader view to accommodate anthropological and sociological approaches. This shift has also had an influence on the techniques which are used in teaching within the classroom setting. The current study focused on providing a comprehensive picture of various sociocultural problems affecting Maltese as a second language (ML2) pedagogy and the depth to which the reported sociocultural issues are significant to ML2 and any second language teaching and learning. This study investigated the challenges experienced by thirty-five ML2 adult learners. Participant interviews constituted the sole data collection tool. The participants, who came from all walks of life and spoke a variety of first language linguistic systems, including Semitic, Romance, Germanic, Slovanic, Indo-European, Indo-Aryan, and Indo-Iranian, experienced challenges regarding their linguistic abilities, culture shock, personalities, memory, and the teaching method. The current study was required to investigate challenges encountered by adult learners of ML2 and to make some recommendations for improving instruction for adult learners.